Annals of the caliphs' kitchens : Ibn Sayyār al-Warrāq's tenth-century Baghdadi cookbook - Ibn Sayyār al-Warrāq, al-Muẓaffar ibn Naṣr, active 10th century?; Nasrallah, Nawal; Murūwah, Saḥbān (Islamic history and civilization, 2007)
Offers a glimpse into the culinary culture of medieval Islam. This book includes hundreds of recipes, anecdotes, and poems, with an extensive Introduction, a Glossary, an Appendix, and color illustration.